Smart Distribution Board Using Blynk - Ramlan, Muhammad Syahir; Ishak, Maizul (Progress in Engineering Application and Technology, 2024)
The Smart Distribution Board features an LCD for real-time monitoring of voltage, current, and power consumption, enhancing safety and efficiency in electrical distribution. It includes a microcontroller (Arduino), ZMPT101B voltage sensor, ACS712 current sensor, 16x2 LCD display, and a servo motor for resetting the RCCB after tripping. Integrated with the Blynk platform, the system allows remote monitoring and control via smartphone. Voltage and current sensors continuously measure parameters displayed on the LCD. Upon detecting an overcurrent, the servo motor resets the RCCB after a delay, restoring electrical supply once the fault clears. Users benefit from real-time status monitoring, trip notifications, and remote RCCB control through Blynk. This system leverages IoT capabilities to provide efficient management of electrical parameters and ensures prompt response to faults, improving overall reliability and user convenience in monitoring and controlling electrical distribution.